Mobiles and 'making do': Exploring the affective, digital practices of refugee women waiting in Greece. (October 2020) - Greene, Alexandra
In the wake of the so-called European migrant crisis, migration scholars have zoomed in on digital technologies and mobility. Seldom addressed, however, are the affective entanglements of migrant digital practices. Yet, as this article argues, waiting is a deeply affective and embodied experience, mediated by information and communications technologies, and tempered both spatially and temporally. Using the cultural politics of emotion as an entry point, and a reflexive and vulnerable methodology, this article explores the digital practices of 15 women waiting in a refugee camp in Greece. In aiming to more justly represent their experiences, this article seeks to move beyond spatial descriptions of migration, as well as to unsettle prevalent discourses of displacement as a liminal condition. Herein, I use the dialectic of strategy and tactics to explore the ways in which smartphones are mobilised in order to 'make do' with protracted experiences of displacement. Three mediated practices of 'making do' are explored: non-mainstream news consumption as a tactic of self-care; mediated family practices as a tactic of hope; and nature photography as a tactic of creativity. In the context of a dehumanising strategy of migration containment, I will argue that everyday tactics of self-care, hope and creativity constitute affective forms of agency.